2015
DOI: 10.14800/ccm.986
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Understanding of Fanconi Anemia Complementation Group D2 Protein (FANCD2) in Human Cancer

Abstract: Fanconi anemia (FA) is a rare human genetic disease, resulting from dysfunction in any of 17 known complementation proteins: FANC-A, B, C, D1, D2, E, F, G, I, J, L, M, N, O, P, Q & S, and other unknowns. Besides the severe bone marrow failure, an extremely high incidence of cancer as well as many other clinic symptoms associated with FA patients, FA cells are known of insufficiency in homologous recombination, DNA mismatch repair, nucleotide excision repair, translesion DNA synthesis, and other molecular defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Swift [26]. However, in patients without FA, these roles were only empirically demonstrated since 2010 by the work we conducted [4852]. With the hidden identity of a more potent central player, the relatively shorter form of FANCD2, V1, has been, unfortunately, recognized as the only representative of the FA pathway for decades.…”
Section: Discussionmentioning
confidence: 99%
“…Swift [26]. However, in patients without FA, these roles were only empirically demonstrated since 2010 by the work we conducted [4852]. With the hidden identity of a more potent central player, the relatively shorter form of FANCD2, V1, has been, unfortunately, recognized as the only representative of the FA pathway for decades.…”
Section: Discussionmentioning
confidence: 99%
“…In early studies, Curcumin, Wortmannin, H-9, and Alsterpaullone were found to inhibit FANCD2 by apoptosis through the NFκB pathway (Chirnomas, 2006). A study further assessed monoketone analogues of Curcumin and found that EF24 was more specific and active against monoubiquitination of FANCD2 (Shen et al 2015). Lastly, a recent study has identified CU2 as a compound that shows potential biochemical ubiquitylation selectivity and activity against the FA pathway (Cornwell, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there have been reports that linked cancer incidence with FA pathway mutations (Shen, 2015). The previously mentioned mutations were reported to cause FA bone marrow failure.…”
Section: Discussionmentioning
confidence: 99%
“…In early studies, Curcumin, Wortmannin, H-9, and Alsterpaullone were found to inhibit FANCD2 by apoptosis through the NFκB pathway (Chirnomas, 2006). A study further assessed monoketone analogues of Curcumin and found that EF24 was more specific and active against monoubiquitination of FANCD2 ( Shen et al 2015). Lastly, a recent study has identified CU2 as a compound that shows potential biochemical ubiquitylation selectivity and activity against the FA pathway (Cornwell, 2019).…”
Section: Discussionmentioning
confidence: 99%